2016
DOI: 10.1128/aac.01130-15
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a Voriconazole-Resistant, Posaconazole-Susceptible Aspergillus fumigatus Isolate in a Lung Transplant Recipient in the United States

Abstract: Molecular characterization of cyp51A from the azole-resistant Aspergillus fumigatus isolate 50593 from a lung transplant patient showed Y121F/T289A changes coupled with a 46-bp tandem repeat (TR46) on the promoter, whereas cyp51A from the pretherapy isolate, A. fumigatus 47381, showed no changes. This is the first reported case of A. fumigatus azole resistance due to Y121F/T289A/TR46 in the United States, suggesting that multiple mutational alterations of cyp51A resulting in high-level azole resistance could o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 14 publications
2
16
1
Order By: Relevance
“…We absolutely agree with Buil et al: in fact, although not reported in this study, we also recovered four additional isolates of A. fumigatus between isolate 1 (AF47381) and the final isolate (AF50593) (4). In fact, all of the Aspergillus isolates recovered between the first and final isolates had identical susceptibility profiles and were all susceptible to voriconazole.…”
supporting
confidence: 58%
“…We absolutely agree with Buil et al: in fact, although not reported in this study, we also recovered four additional isolates of A. fumigatus between isolate 1 (AF47381) and the final isolate (AF50593) (4). In fact, all of the Aspergillus isolates recovered between the first and final isolates had identical susceptibility profiles and were all susceptible to voriconazole.…”
supporting
confidence: 58%
“…The selection of TR 46 /Y121F/T289A alteration during long-term voriconazole therapy has been suggested recently24. However, in the absence of convincing proof it is now well accepted that these alterations are environmental DMI fungicide-driven25.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in 1990s another group of azoles, called triazoles, was developed, such as fluconazole and itraconazole Sphingolipids as targets for treatment of fungal infections Review malian body fluids and absorbance by host tissues, allowing them to be widely used for the treatment systemic fungal infections [40]. Despite this success, resistance cases have been increasingly reported, thus a new generation of triazoles, such as voriconazole, posaconazole and ravuconazole ( Figure 2K-M), has been developed to overcome fluconazole and itraconazole resistance, although the emergence of resistance has been recently observed also for these new drugs [41][42][43][44][45].…”
Section: Current Classes Of Antifungalsmentioning
confidence: 99%